Under pressure: Romania's labour market review. The labour supply and demand - Luminita Chivu; George Georgescu (Romanian Academy, National Institute for Economic Research, 2020)
The labour market in Romania is under the pressure of divergent factors, at the intersection of the labour demand and supply determinants. This paper is focusing on quantitative and qualitative analysis of the labour market in Romania, trying to identify its imbalances and to find ways for their mitigation considering the main trends, including the European labour market developments. From the perspective of the labour supply, despite massive emigration, is found that Romania still has an important human potential including an unused workforce reserve, but the performances of the education and training should improve for increasing the quality of competences and skills needed on the labour market. Looking at the demand for labour force, although under the circumstances of the lack of information for an accurate assessment, starting with 2012, as a general trend, the number of jobs created exceeded the number of job vacancies, the new created companies, with a higher degree of technology and more competitive, having significantly contributed to the increase in the employment rate. However, imbalances between the labour demand and supply have emerged and are growing, likely to become a severe obstacle hindering the development of Romania in the medium and long term.
Keywords: E60; F22; F66; I20; J08; J10; J21; J23; J61; 330; demographic trends; population aging; emigration; demographic and economic dependency ratio; labour market demand and supply; labour market tensions; internal mobility; labour shortages